Evaluation of health-related quality of life in hemolytic uraemic syndrome patients treated with eculizumab: a systematic evaluation on basis of EMPRO. (15th October 2018) - Mukherjee, Anwesha A.; Kandhare, Amit D.; Bodhankar, Subhash L.
Abstract: Background: Hemolytic uraemic syndrome (HUS) is progressive renal failure disease and determination of their quality of life (QoL) on the basis of patient-reported outcomes (PROs) are becoming increasingly important in the economic evaluations for its treatment with eculizumab (ECU). Aim: To perform the systematic evaluation of QoL in HUS patients treated with ECU on the basis of Evaluating Measures of Patient Reported Outcomes (EMPRO) tool. Materials and methods: A systematic review was conducted in PubMed, EMBASE, the Cochrane Library, CINAHL and Google Scholar till September 2016 by two independent researchers. Each identified instrument was evaluated for its quality of performance by using the EMPRO tool for its overall score and seven attribute specific scores (range 0–100, worst to best). Results: Five different PROs instruments were identified from 10 articles ( n  = 112) which showed eculizumab significantly improves health-related quality of life (HRQOL) in atypical HUS (aHUS) patients. Amongst five instruments viz. EuroQol five dimensions questionnaire (EQ-5 D), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F), Headache Impact Test-6 (HIT-6), 36-Item Short Form Health Survey (SF-36) and Visual Analogue Scale (VAS), the overall EMPRO score was higher for VAS (73.83) and EQ-5 D (73.81). Whereas, FACIT-F and HIT- 6 were just able to meet the minimal threshold of EMPRO scoring (50.24 and 59.09, respectively). Conclusions: Evidence from present investigation support that eculizumab significantly improves HRQoL in patients with aHUS furthermore, EQ-5 D and VAS instrument should be recommended for assessing HRQoL in them. However, selection of PRO instrument for determination of QoL in HUS entirely depend upon the study requirements.